COACHING CLINIC PENGUKURAN OLAHRAGA BAGI KLUB BOLAVOLI TUNAS DESA / KEC. LOHBENER, KAB. INDRAMAYU - Hendro Wardoyo; Tirto Apriyanto; Muhamad Ilham (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract The main objectives of community service activities for the Superior Assisted Area are coaches, coaches and players of the Tunas Volleyball Club in Lohbener village, Indramayu district, Indramayu district. Service activities are carried out by providing knowledge both theoretical and practical about measurement knowledge and skills, especially in physical aspects and procedures for their implementation. The participants of this activity are coaches, coaches and volleyball players of Lohbener village, Indramayu district, kab. Indramayu had 25 participants. Community service activities for the Superior Assisted Areas regarding coaching clinics have been carried out well. Through this service activity produced 25 coaches, coaches and athletes who have competence about knowledge and measurement skills, especially in the physical aspects and procedures for their implementation. This community service activity in the Ungulan Fostered area received an enthusiastic response from the participants of the activity. This is evident from the coach's satisfaction with coaching clinic activities is very high, which is 88.40%. AbstrakTujuan utama kegiatan pengabdian kepada masyarakat Wilayah Binaan Unggulan adalah pelatih, pembina dan pemain Klub Tunas bola voli desa Lohbener, kec. Indramayu, kab. Indramayu. Kegiatan pengabdian dilakukandengan pemberian pengetahuan baik teori maupun praktek tentang pengetahuan dan keterampilan pengukuran terutama dalam aspek fisik dan prosedur pelaksanaannya. Peserta kegiatan ini adalah pelatih, pembina dan pemain bola voli desa Lohbener, kec. Indramayu, kab. Indramayu sebanyak 25 peserta. Kegiatan pengabdian kepada masyarakat Wilayah Binaan Unggulan mengenai coaching clinic telah terlaksana dengan baik. Melalui kegiatan pengabdian ini menghasilkan 25 pembina, pelatih dan atlet yang memiliki kompetensi tentang pengetahuan dan keterampilan pengukuran terutama dalam aspek fisik dan prosedur pelaksanaannya. Kegiatan pengabdian kepada masyarakat wilayah Binaan Ungulan ini mendapatkan respon yang antusias dari para peserta kegiatan. Hal ini terbukti dari kepuasaan pelatih terhadap kegiatan coaching clinic sangat tinggi yaitu sebesar 88,40%.